Bat Trang ceramics 14th - 19th centuries - Phan Huy Lê.; Nguyễn Đình Chiến; Nguyễn Quang Ngọc. (Hà Nội : Thế giới, 2004)
Bat Trang ceramics: 14th-19th centuries; Plates, figures, rubbings, inscriptions.
Keywords: Ceramics; Bat Trang -- Ceramics -- 14th - 19th centuries